2015
DOI: 10.1111/tme.12194
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro study comparing two dose regimes of fresh frozen plasma on conventional and thromboelastographic tests of coagulation after major hepatic resection

Abstract: Despite the rise in INR after hepatectomy, VET do not show evidence of hypocoagulability. In vitro addition of FFP had no significant effect on TEG parameters. Clinical use of FFP in this situation is questionable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…These findings therefore question the practice of administering prophylactic FFP before invasive procedures purely to reduce a perceived bleeding risk if the INR ≤ 2, or indeed the need to delay removal of epidural catheters until the INR returns to normal range. Although transfusion of FFP will partially correct an elevated INR following liver resection, it has no measurable effect on viscoelastic parameters that are already within normal range . Our data support the need for early initiation of thromboprophylaxis, and this is paradoxically of even more importance in patients with more extensive resections and consequently higher INR values.…”
Section: Discussionmentioning
confidence: 50%
“…These findings therefore question the practice of administering prophylactic FFP before invasive procedures purely to reduce a perceived bleeding risk if the INR ≤ 2, or indeed the need to delay removal of epidural catheters until the INR returns to normal range. Although transfusion of FFP will partially correct an elevated INR following liver resection, it has no measurable effect on viscoelastic parameters that are already within normal range . Our data support the need for early initiation of thromboprophylaxis, and this is paradoxically of even more importance in patients with more extensive resections and consequently higher INR values.…”
Section: Discussionmentioning
confidence: 50%
“…While immediately post resection both standard coagulation testing and TEG values indicated a normocoagulable state, up to POD5 TEG revealed a hypercoagulable state with decreased r time, whereas standard coagulation testing indicated a hypocoagulable status. This discrepancy between standard coagulation testing and TEG was also observed in the Schofield et al, 29 Banz et al 30 and Tanner et al 18 studies. Specifically, despite the prolongation in INR after hepatectomy, TEG did not demonstrate evidence of hypocoagulability in the study by Schofield et al 29 In another study, microparticle tissue factor and procoagulant activity increased after liver resection along with overall coagulation as assessed by TEG, whereas standard coagulation testing indicated normocoagulability.…”
Section: Standard Coagulation Testing and Viscoelastic Testing Parame...mentioning
confidence: 59%
“…This discrepancy between standard coagulation testing and TEG was also observed in the Schofield et al, 29 Banz et al 30 and Tanner et al 18 studies. Specifically, despite the prolongation in INR after hepatectomy, TEG did not demonstrate evidence of hypocoagulability in the study by Schofield et al 29 In another study, microparticle tissue factor and procoagulant activity increased after liver resection along with overall coagulation as assessed by TEG, whereas standard coagulation testing indicated normocoagulability. 30 Similar findings were observed in the study by Tanner et al with TEG demonstrating a hypercoagulable profile in 64%, 33%, 39% and 36% of patients following hepatectomy on POD0, POD1, POD3 and POD5, respectively.…”
Section: Standard Coagulation Testing and Viscoelastic Testing Parame...mentioning
confidence: 59%
See 1 more Smart Citation
“…In contrast, hemostasis management guided by viscoelastic testing has been shown to reduce transfusion requirements in patients with cirrhosis [19,20]. DePietri et al [42], Schofield et al [43], and Mallet et al [44] demonstrated a disagreement between conventional coagulation testing and viscoelastic testing regarding hypo- and hypercoagulability in patients undergoing major liver resection. Herbstreit et al [45] is in -line with our finding that CT in thromboelastometry shows poor correlation with both PT and aPTT in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%